FINANCIAL MANAGEMENT BEHAVIOR PADA PENGGUNA PAYLATER DALAM PERSPEKTIF THEORY OF PLANNED BEHAVIOR - Putu Eka Widiastuti Maha Dewi; Fadilla Cahyaningtyas (POLITEKNIK LP3I JAKARTA, 2024)
The purpose of this study was to determine the financial management behavior of employees in the administrative department of a retail company in Malang. This study uses quantitative methods and a Likert scale for the measurement scale. The independent variable consists of financial knowledge, financial socialization and financial experience, while the dependent variable is financial management behavior. The total number of active respondents using paylater was obtained by 96 respondents by distributing questionnaires online. The results showed that financial knowledge had a positive effect on financial management behavior, while financial socialization and financial experience had no effect on financial management behavior. The ability to manage finances can influence an individual's financial condition in the future. This study can be useful as a reference for various parties, especially Paylater users to be wiser in making financial decisions and to be able to improve good financial management behavior. Keywords: Financial Knowledge, Financial Socialization, Financial Experience, Financial Management Behavior